Study on the Performance and Green Degree Evaluation of the Reference Cement–Sulfoaluminate Cement Composite System - Yi Shi; Zhenping Shi; Lei Yuan; Tao Wang (Advances in Civil Engineering)
With the large-scale construction of infrastructure such as high-speed railways and the rapid development of building industrialization and prefabricated buildings, the precast concrete industry has ushered in vigorous vitality. However, there are many tricky problems such as high-energy consumption and unstable long-term performance in the existing production technology of steam-cured concrete. Based on the current research on concrete early strength technology, this paper focuses on the early strength performance and greenness evaluation of the reference cement–sulfoaluminate cement (C–SAC) system. The results confirm that when the 30% mineral admixture—60% C–10% SAC system is mixed with the composite early strength agent, the 1 day strength of mortar can reach 38.0 MPa under the condition of 45°C steam curing. The water absorption is 1.1% after 28 days. The carbon emission of the system (32.1%) is lower than that of the reference cement, and the production energy consumption and the initial resource energy are reduced by 14.4% and 8.2%, respectively. This paper provides a promising strategy for the development of low-carbon, and early strength concrete and ultimately provides technical support for the realization of high-quality and green production of precast concrete components.